Effect of non-parallel applicator insertion on microwave ablation zone size and shape - White, Austin (Kansas State University, 2018)
Microwave ablation is clinically used to thermally ablate cancerous tissue in the liver and other organs. When treating large tumor volumes, physicians may use multiple antennas simultaneously. Multiple antennas can ablate a larger tissue volume while using the same total power as a single antenna. Pre-clinical simulation and experimental studies most often presume parallel insertion of antennas. However, due to anatomical constraints, such as the presence of ribs and the diaphragm, it is often challenging to insert antennas in a parallel fashion in practice. Previous studies have attempted to analyze the effect of non-parallel antenna insertion on ablation outcome using computational and experimental approaches; however, they were limited because they did not account for dynamic temperature-dependent changes in tissue electrical properties in simulations and employed limited experimental validation. In this thesis, we have developed improved models of multiple-antenna microwave ablation, including accounting for the effects of temperature-dependent changes in tissue properties. We have also developed a system for experimental assessment of ablation zone profiles in ex vivo tissues. By utilizing 3D printing, we have constructed a device to precisely position antennas within experimental tissue samples and allows for accurate sectioning of the ablation zone relative to the plane of antenna insertion. Furthermore, we implemented image processing techniques for quantifying the size and shape of experimental ablation zones. This enables more accurate and repeatable comparisons of ablation profiles between simulations and experiments. We found that for an inter-antenna spacing in the range of 10 – 20 mm, simulations and experiments indicated that the ablation zone volumes may change by up to 30% due to non-parallel antenna insertion.
Keywords: Ablation; Non-parallel; Microwave; Image processing; Ex-vivo bovine liver; 3D printing